Procedimento para promover variação na topografia de respostas verbais em crianças com desenvolvimento atípico - Romano, Claudia (2005)
The current research studied the possibility of establishing verbal responses that initialize verbal interactions and variation on its topography in two children with atypical development and a restrict verbal repertoire. The verbal responses in matter are defined as verbal responses under non-verbal discriminative stimuli control and the variation on its topography as the emission of differing responses in and every trial and from those (directly) trained by the researcher. Therefore three topographies of different responses were trained in two situations using a multiple baseline design between situations. Training occurred in individualized sessions during approximately 70 minutes in which participants went following three distinct situations: class (15 times); break (15 times) and toilet (3 times) being 2 minutes in each situation. The baseline consisted of recording the occurrence or not of any verbal response that initialize a verbal interaction during the first 10 seconds of each situation. During Intervention phase three different topographies of responses that initialize verbal interaction were trained in each situation by the experimenter: first at class situation and then at break situation. Visual, echoic and intraverbal prompts were displayed at the verbal responses training. Results showed an effective procedure to produce verbal responses to initialize a verbal interaction independently of verbal prompts in both participants and both situations. At the end of the training phase topographies of responses differing from baseline and trained responses were observed. The results didn t show the occurrence of a clear generalization between situations. Effects of simultaneously training of more than one topography response and the necessity of discussing procedures that increase the likelihood of generalized and varied topography verbal response emission are debated.